Análisis crítico de la metodología implementada por el IDEAM y las empleadas en el ámbito internacional para la definición del índice de escasez del agua superficial. (2018)
The following document approach the thematic from methodology for calculation of the scarcity index design by IDEAM (by its acronym in Spanish), for which will aboard the following topics: description from some calculation methodologies used at international levels, exactly in countries such as USA, Israel, Netherlands and Canada; some critics by national authors about the methodology, advantage and disadvantage from the scarcity index and finally the proposed readjustments for the index calculation. Additionally would be design a practical guide for the calculation taking in consideration the obtained results by the performed analyzes, it will be suggested some improvements for the currently methodology with new ranges to measure the scarcity index, it will be presented the conclusions and recommendations and finally all the procedure will be applied in a representative case. This document is presented as a tool to facilitate the use to estimate the scarcity index, being useful in the decision making in the correct use of water resources in the country.